Aid work as moral labour. (September 2016) - Fechter, Anne-Meike
This paper argues that some of the engagements and practices of international aid workers can be productively understood as forms of moral labour. Taking Hardt's concept of 'immaterial labour' (1999) as a point of reference, the paper examines the moral practices that aid workers engage in the course of their work and personal lives. Much of the relevant literature focuses on the humanitarian imperative – that is, the implied moral responsibility of better-off nations and individuals to assist others in need. Less extensively, some development literature has adopted the understanding of aid and development assistance in moral frameworks of the gift, or 'doing good'. What happens, though, in terms of experienced and practiced moralities in the concrete situations and scenarios generated by such helping imperatives? Drawing on ethnographic fieldwork among aid workers in Cambodia, the paper examines some of the perhaps inevitable moral entanglements which these workers find themselves in, and have to negotiate. The analytical benefits of framing these efforts as 'moral labour' include a broadened understanding of how morality matters in aid beyond the helping imperative, as well as a recognition that the significance of this labour does not rest on products that may result from it, but lies in the performance of the labour itself.